Subtract 10 and collect terms to get the variable term by itself on the left.
... 4c = 24
Divide by the coefficient of the variable, 4.
... c = 6
The appropriate choice is the second one:
... 6
_____
You don't actually have to sove the equation to find the right answer. You just need to see which answer works.
-6: 5(-6) -(-6) +10 = -14 ≠ 34
6: 5(6) -(6) +10 = 34 . . . . . . . this answer works (you can stop here)
11: 5(11) -(11) +10 = 54 ≠ 34
-11: 5(-11) -(-11) +10 = -34 ≠ 34
Remember the distance formula
![S=\sqrt{(5+3)^{2}+(-1-2)^{2} }](https://tex.z-dn.net/?f=S%3D%5Csqrt%7B%285%2B3%29%5E%7B2%7D%2B%28-1-2%29%5E%7B2%7D%20%7D)
![S=\sqrt{8^{2}+(-3)^{2} }](https://tex.z-dn.net/?f=S%3D%5Csqrt%7B8%5E%7B2%7D%2B%28-3%29%5E%7B2%7D%20%7D)
![S=\sqrt{64+9}](https://tex.z-dn.net/?f=S%3D%5Csqrt%7B64%2B9%7D)
![S=\sqrt{73}](https://tex.z-dn.net/?f=S%3D%5Csqrt%7B73%7D)
F(-1) = 2(-1)^2 + 8(-1)
= 2(1) + (-8)
= -6
<h3><u>Given</u>:-</h3>
Side(a) of the cube =
.
<h3><u>To Find</u>:-</h3>
Surface Area of the cube with side ![\sf{\frac{1}{3}ft.}](https://tex.z-dn.net/?f=%5Csf%7B%5Cfrac%7B1%7D%7B3%7Dft.%7D)
<h3><u>Formula Used</u>:-</h3>
Surface area of cube = ![\sf{6a^2}](https://tex.z-dn.net/?f=%5Csf%7B6a%5E2%7D)
<h3><u>Solution</u>:-</h3>
Surface area of cube =
(putting the value of a from the above given)
![\sf{=\:6×(\frac{1}{3})^2}](https://tex.z-dn.net/?f=%5Csf%7B%3D%5C%3A6%C3%97%28%5Cfrac%7B1%7D%7B3%7D%29%5E2%7D)
![\sf{=\:6×\frac{1}{9}}](https://tex.z-dn.net/?f=%5Csf%7B%3D%5C%3A6%C3%97%5Cfrac%7B1%7D%7B9%7D%7D)
![\sf{=\:\frac{6}{9}}](https://tex.z-dn.net/?f=%5Csf%7B%3D%5C%3A%5Cfrac%7B6%7D%7B9%7D%7D)
![\sf{=\:\frac{2}{3}ft^2}](https://tex.z-dn.net/?f=%5Csf%7B%3D%5C%3A%5Cfrac%7B2%7D%7B3%7Dft%5E2%7D)
Therefore, surface area of the given square = ![\sf{=\:\frac{2}{3}ft^2}](https://tex.z-dn.net/?f=%5Csf%7B%3D%5C%3A%5Cfrac%7B2%7D%7B3%7Dft%5E2%7D)
__________________________________
Hope it helps you:)